Tyler's Herbs of choice : the therapeutic use of phytomedicinals - Awang, Dennis V. C. (Taylor & Francis, 2009)
Does Echinacea fight the common cold? Does St John's Wort (SJW) really counteract depression? What about chondroitin for joint health? This title combines the scientific aspects of herbal medicine, phytomedicine, and pharmacognosy with the modern clinical trials that support the rationale for using plant products in healthcare.- Resumé vydavatel